Observed Changes (1970-1999) in Extreme Hydroclimatic Events in Central America - Hidalgo León, Hugo G. (2018)
Previous studies have shown that most of Central America has been experiencing warming trends during the last 30-50 years, while precipitation annual totals have not changed much. Warming alone can exacerbate the effects of droughts as potential evapotranspiration increases, causing drier soils and higher aridity. It is evident that the demand of water from the atmosphere has becoming larger. Central America is a region known to be impacted by wet and dry extreme events. Within the scenario of higher aridity, severe and sustained droughts can produce a larger number of impacts in the region. But also, wet extreme events are the cause of severe impacts. Analysis of observed precipitation extremes show a trend toward more severe events in recent years. In this presentation, recent trends in different hydroclimatic variables as well as in metrics representing extreme events are analyzed.